THE CONVERGENCE OF AI AND SOCIALPRENEURSHIP: TECHNOLOGY-BASED BUSINESS MODELS TO ADDRESS SOCIAL CHALLENGES IN THE DIGITAL AGE - Kemal Al Kindi Mulya; Naomi Analisa Simanjuntak (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the convergence between artificial intelligence (AI) technology and social entrepreneurship in developing technology-based business models to overcome social challenges in the digital era. Using a qualitative literature review method with thematic content analysis of the scientific literature for the period 2020-2025, this study explores the integration of AI technology in the social entrepreneurship ecosystem, ethical challenges and emerging social impacts, and the development of sustainable business models based on AI technology. The results show that the convergence of AI and social entrepreneurship is creating a fundamental transformation in approaches to social problem-solving through process automation, service personalization, and resource allocation optimization. Platform-based, subscription-based, and freemium business models have proven effective in creating financial sustainability while maintaining measurable social impact. However, the implementation of AI in a social context faces complex challenges in the form of algorithmic bias, data security, digital divides, and technological dependencies that require a comprehensive ethical framework. The study concludes that the success of the convergence of AI and social entrepreneurship depends on the ability to maintain a balance between technological innovation and human value through cross-sectoral strategic collaboration in developing an inclusive and sustainable ecosystem.